2022
DOI: 10.1038/s41467-022-31689-3
|View full text |Cite
|
Sign up to set email alerts
|

Longest sediment flows yet measured show how major rivers connect efficiently to deep sea

Abstract: Here we show how major rivers can efficiently connect to the deep-sea, by analysing the longest runout sediment flows (of any type) yet measured in action on Earth. These seafloor turbidity currents originated from the Congo River-mouth, with one flow travelling >1,130 km whilst accelerating from 5.2 to 8.0 m/s. In one year, these turbidity currents eroded 1,338-2,675 [>535-1,070] Mt of sediment from one submarine canyon, equivalent to 19–37 [>7–15] % of annual suspended sediment flux from present-day… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 68 publications
1
50
0
Order By: Relevance
“…Recent studies have shown that the frequency of occurrence of turbidity currents is higher than previously proposed (Stevenson et al 2018, Hage et al 2019, Heijnen et al 2022 and without the catastrophic characteristics reported for high turbulent turbidity currents (e.g., Mulder et al 1997).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Recent studies have shown that the frequency of occurrence of turbidity currents is higher than previously proposed (Stevenson et al 2018, Hage et al 2019, Heijnen et al 2022 and without the catastrophic characteristics reported for high turbulent turbidity currents (e.g., Mulder et al 1997).…”
Section: Discussionmentioning
confidence: 71%
“…Much less is known about the flow properties and velocities when turbidity currents become unconfined. As also shown by recent field measurements, largescale turbidity currents can travel long distances, for example > 100 km before sedimentation in unconfined settings takes place (Stevenson et al 2018, Talling et al 2022. As a consequence, turbidity currents form preferential paths, building submarine channels or canyons along areas with high slopes.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recent field-scale flow monitoring offshore from river mouths has recognised the combined effect of elevated river discharge and tidal drawdown on flow generation (Ayranci et al, 2012;Clare et al, 2016;Hage et al, 2019;Hill and Lintern, 2021;Hughes Clarke et al, 2012;Lintern et al, 2016;Talling et al, 2022). For example, elevated river discharge may rapidly deposit sediment on the delta-lip, thus preconditioning the delta slope to failure.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the continental slope was conventionally perceived to primarily experience sediment bypass in source-to-sink studies, the net bypass character of the slope is the result of alternation of deposition and erosion over various magnitudes and time-scales (e.g., Prather et al, 2017). Although the basin-plain is typically considered as a sink, the same concept applies, with varying degrees of erosion and deposition occurring in the deep-ocean (e.g., Talling et al, 2022). Hence, the deep-sea has a diverse capacity for sediment storage but also great potential for redistribution (e.g., Shumaker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%